A non-invasive wearable sweat biosensor with a flexible N-GQDs/PANI nanocomposite layer for glucose monitoring - Lin, Yu-Chi; Rinawati, Mia; Chang, Ling-Yu; Wang, Yu-Xuan; Wu, Yu-Ting; Yen, Yi-Han; Chen, Kuan-Jung; Ho, Kuo-Chuan; Yeh, Min-Hsin (Sensors and actuators. B, Chemical, 2023)
Understanding the levels change in biomarkers over time, especially glucose, is crucial for diabetics to inform early therapy. Recently, wearable sweat biosensors which operate in a non-invasive way have raised attention, providing continuous monitoring of the severity level. Nevertheless, the key challenges are that multiplexed motions may result in undesirable metal cracking by the rigid electrocatalytic layer, leading to decreased sensitivity and stability. In this work, we designed an N-GQDs anchored PANI matrix to realize flexible wearable biosensors with high detection accuracy. Upon the enhanced electron transfer by N-GQDs, N-GQDs/PANI nanocomposite offers greater sensitivity in H2O2 detection compared to pristine PANI, resulting in a sensitivity of 68.1 ± 1.11 and 44.06 ± 2.1 μA mM−1 cm−2, respectively. Moreover, after the glucose oxidase (GOx) immobilization, GOx/N-GQDs/PANI-based biosensors had shown excellent performance for glucose detection in artificial sweat. Precise glucose detection was also maintained after integrating into a flexible electrode, the sensitivity of the GOx/N-GQDs/PANI-based biosensor had retained 93.2 % with no apparent cracks in the morphology of the nanocomposite layer, compared to GOx/Pt-based one (71.3 %) toward glucose detection after a continuous bending test. Thus, the N-GQDs/PANI nanocomposite layer can provide reliable long-term monitoring with robust electrodes for non-invasive human sweat glucose monitoring on a wearable biosensor. [Display omitted] •A novel developed nanocomposite layer of N-GQDs/PANI was proposed.•The relationship between the N doping levels of N-GQDs and PANI toward H2O2 detection has explored.•The N-GQDs modified PANI successfully lowered the charge transfer resistance.•GOx/N-GQDs/PANI can maintain its excellent sensitivity under continuous bending test.